2002
DOI: 10.1051/lait:2001005
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins of propionic acid bacteria

Abstract: -Dairy propionibacteria produce a number of inhibitory compounds like propionate, acetate and diacetyl. In addition, a number of strains produce bacteriocins. Unlike lactic acid bacteria, they often produce compounds that inhibit Gram (-) bacteria as well as yeasts and molds. These dairy propionibacteria are food-grade organisms and their bacteriocins may be of interest as food preservatives. Some of their bacteriocins have been characterized. Most are heat-stable peptides containing less than 100 amino acid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…These strains also exhibited antimicrobial activities corresponding to propionicin T1 and PAMP activities, indicating that both genes were expressed. A comparison of the studies reviewed by Holo et al (9) and the results presented here suggests that some of the previously reported antimicrobial activities of propionibacteria may be attributed to some of the peptides that have been identified already. The results described in this paper show the importance of screening potential bacteriocin producers for bacteriocin genes that already have been characterized and for the corresponding bacteriocin production in order to avoid duplication of research efforts.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…These strains also exhibited antimicrobial activities corresponding to propionicin T1 and PAMP activities, indicating that both genes were expressed. A comparison of the studies reviewed by Holo et al (9) and the results presented here suggests that some of the previously reported antimicrobial activities of propionibacteria may be attributed to some of the peptides that have been identified already. The results described in this paper show the importance of screening potential bacteriocin producers for bacteriocin genes that already have been characterized and for the corresponding bacteriocin production in order to avoid duplication of research efforts.…”
supporting
confidence: 66%
“…However, these antimicrobial compounds have several biochemical features in common, such as inhibitory spectrum, stability, hydrophobicity, and cationic nature (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of propionicin T1 and pro-PAMP is prevalent in P. jensenii and P. thoenii strains but has not been identified as occurring in P. freudenreichii (12). In fact, no bacteriocin has been purified from P. freudenreichii, although the antimicrobial potential of this organism has frequently been demonstrated (1,19,31).Characterization of bacteriocins from P. freudenreichii is of special interest, since this species is the most important secondary starter in the production of Swiss-type cheeses. In this work we describe the molecular and genetic characterization of propionicin F, the first bacteriocin isolated from P. freudenreichii.…”
mentioning
confidence: 99%
“…PAB also have a potential use as protective cultures for inhibition of pathogens and food spoilage organisms (30,31). The antimicrobial capacity of PAB is only partly due to the production of organic acids, and it has become evident that PAB also produce other biologically active substances such as bacteriocins (4,7,9,13,26). Recently, Faye et al (9) characterized the propionicin T1 bacteriocin from Propionibacterium thoenii.…”
mentioning
confidence: 99%